2016
DOI: 10.1111/bjh.14307
|View full text |Cite
|
Sign up to set email alerts
|

Red cell alloimmunisation in patients with different types of infections

Abstract: Red cell alloantigen exposure can cause alloantibody-associated morbidity. Murine models have suggested that inflammation modulates red cell alloimmunisation. This study quantifies alloimmunisation risks during infectious episodes in humans. We performed a multicentre case-control study within a source population of patients receiving their first and subsequent red cell transfusions during an 8-year follow-up period. Patients developing a first transfusion-induced red cell alloantibody (N = 505) were each comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 38 publications
3
48
1
1
Order By: Relevance
“…Notably, Evers et al . recently found that MDS was associated with a lower relative risk for alloimmunization, which contrasts with our findings. However, it is important to note that the association we observed was specifically among hyper‐responders (i.e.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Notably, Evers et al . recently found that MDS was associated with a lower relative risk for alloimmunization, which contrasts with our findings. However, it is important to note that the association we observed was specifically among hyper‐responders (i.e.…”
Section: Resultscontrasting
confidence: 99%
“…b). The findings regarding sepsis in our study, which referred to patients categorized as having severe infections, are consistent with earlier studies , which indicated lower alloimmunization rates among patients with bacteraemia. It is unclear why the disorders in Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Multiple studies have established that certain inflammatory disorders and inflammatory stimuli increase the frequency and magnitude of alloimmune responses to RBC Ags (1216, 1921). However, the molecular mechanisms underlying these findings have not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…Also, similar to prior murine studies, a recent human study reported that inflammation associated with different infections can have distinct effects. Patients with viremia were reported to have increased rates of alloimmunization, whereas patients with Gram-negative bacterial infections had lower rates (16). These associations indicate that specific pathways activated in some inflammatory conditions, such as autoimmunity and viral infections, promote RBC alloimmunization.…”
mentioning
confidence: 99%